Alteration of Ileal lncRNAs After Duodenal–Jejunal Bypass Is Associated With Regulation of Lipid and Amino Acid Metabolism - Liang, Yongjun; Yu, Minghua; Wang, Yueqian; Li, Mengyi; Zhang, Zhongtao; Qiao, Zhengdong; Zhang, Peng (Frontiers in Physiology, 2022)
Metabolic and bariatric surgery (MBS) can generate a drastic shift of coding and non-coding RNAs expression pattern in the gastrointestinal system, which triggers organ function remodeling and may induce type 2 diabetes (T2D) remission. Our previous studies have demonstrated that the altered expression profiles of duodenal and jejunal long noncoding RNAs (lncRNAs) after the duodenal-jejunal bypass (DJB), an investigational procedure and research tool of MBS, can improve glycemic control by modulating entero-pancreatic axis and gut-brain axis, respectively. As an indiscerptible part of intestine, the ileal lncRNAs expression signatures after DJB and the critical pathways associated with postoperative correction of impaired metabolism need to be investigated too. High-fat diet-induced diabetic mice were randomly assigned into two groups receiving either DJB or sham surgery. Compared to the sham group, 1425 dysregulated ileal lncRNAs and 552 co-expressed mRNAs were identified in DJB group. Bioinformatics analysis of the differently expressed mRNAs and predicted target genes or transcriptional factors indicated that the dysregulated ileal lncRNAs were associated with lipid and amino acid metabolism related pathways. Moreover, a series of lncRNAs and their potential target mRNAs, specifically NONMMUT040618, Pxmp4, Pnpla3, and Car¬5a, were identified on the pathway. In conclusion, DJB can induce remarkable alteration of ileal lncRNAs and mRNAs expression. The role of ileum in DJB tends to re-establish the energy homeostasis by regulating lipid and amino acid metabolism.